Rosyjskojęzyczne środowisko literackie przeciwko wojnie Rosji z Ukrainą. Próba rekonesansu - Brzykcy, Jolanta (Przegląd Wschodnioeuropejski, 2026)
The article reviews the attitudes of Russian writers towards Russia’s war against Ukraine, which has been going on since 2014 and has taken a full-scale form since 2022. It focuses on the anti-war wing of the contemporary Russian-language literary scene. The following issues were discussed: the impact of the war on the psychological condition of writers and poets openly opposing the Kremlin’s policy (declared feelings of anger, indignation, shock, shame at Russia’s aggression against Ukraine), the forms of protest they undertake (charity work for Ukrainians, participation in fund-raisers, emigration from the country), creative strategies, the conditions of artistic activity in exile (confrontation with anti-Russian sentiments present in the Western community) and in Russia (Vladimir Putin’s repressive cultural policy) are discussed. The context for the analysis of the part of the Russian literary scene in opposition to the Kremlin is Emmanuel Lévinas’s thought on war as an ontological condition.